Organic Reactions on Water - ชัยยานุรักษ์กุล, อารดา (KKU Science Journal, 2015)
It has been known that most of organic reactions have to be conducted in organic solvents due to solubility of organic substrates and reagents in organic solvents. However, it has been found recently that many classical organic reactions can be carried out using water as a solvent. This has raised much attention on organic reactions on water due to many advantages of water over organic solvents both handling and environmental aspects. The most important aspects are high reaction rate and selectivity of the organic reactions on water over organic solvents. Therefore, organic reactions on water have been more studied and it is believed that hydrophobic effect plays a role in bringing non-polar substrates and reagents together to make organic reactions on water possible and proceed with high reaction rate and selectivity.